Updated Evidence of the Association Between Elevated Serum Uric Acid Level and Psoriasis - Zhang, Ying; Liu, Liu; Sun, Xiaoying; Li, Hongjin; Wang, Yifei; Zhou, Min; Hua, Liang; Li, Bin; Li, Xin (Frontiers in Medicine, 2021)
Background: Our earlier meta-analysis showed that the correlation between psoriasis and hyperuricemia might be region-dependent and that hyperuricemia was more common in patients with psoriasis in Western Europe. However, no further analysis could be conducted owing to the scarcity of data. Objective: Our study aimed to further explore the association between psoriasis and hyperuricemia. Methods: Six databases (PubMed, Embase, the Cochrane Central Register of Controlled Trials, the China National Knowledge Infrastructure database, the Chinese Scientific Journals Full Text Database, and the Wanfang Data Knowledge Service Platform) were searched for studies published between January 1980 and February 2021. Results: The search strategy yielded 291 relevant studies, of which 27 observational studies were included in this analysis. Serum uric acid (SUA) levels (mean difference [MD] 0.99, 95% confidence interval [CI] 0.48–1.49, P = 0.0001) and hyperuricemia frequency (odds ratio [OR] 5.39, 95% CI 1.88–15.40, P = 0.002) were higher in the psoriasis group than in the control group, and the subgroup differences were significant. In addition, SUA levels were significantly higher in patients with moderate to severe psoriasis from European and American countries (MD 0.89, 95% CI 0.18–1.60, P = 0.01) and Southeast Asia (MD 1.79, 95% CI 0.55–3.02, P = 0.004), while no significant differences were found between the Middle East subgroup (MD 0.63, 95% CI −0.33 to 1.59, P = 0.20). Similar results were obtained from the meta-analysis of SUA levels in patients with metabolic syndrome, obesity, or a special type of psoriasis (such as arthritic or erythrodermic psoriasis). Conclusions: Our meta-analysis study provides extended data regarding the correlation between psoriasis and hyperuricemia and the differences in SUA levels between psoriasis patients and controls in Southeast Asia, the Middle East, and European and American countries. Patients with moderate to severe psoriasis in European and American countries and Southeast Asia or those with metabolic syndrome and obesity were more likely to have higher uric acid levels. Systematic Review Registration: PROSPERO, identifier: CRD42014015091.